2020
DOI: 10.32598/jams.23.1.6005.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Stress Coping Strategies and Difficulties in Emotion Regulation Mediated by Marital Life Quality in Married Women With Breast Cancer

Abstract: Background and Aim The purpose of this study was to evaluate the relationship between stress coping strategies and difficulties in emotion regulation mediated by marital life quality in married women with breast cancer. Methods & Materials This is a descriptive correlational study. The study population included all married women with breast cancer in Amol and Babol cities of Iran in 2018. Of these, 385 were selected through a convenience sampling technique. The research instruments were Ways Of Coping Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thought appeasement and avoidance of threaten-ing stimuli do not eliminate disturbing thoughts; instead, they provide fodder for irritating rumination. As an avoidance strategy, thought appeasement could create more mental worries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thought appeasement and avoidance of threaten-ing stimuli do not eliminate disturbing thoughts; instead, they provide fodder for irritating rumination. As an avoidance strategy, thought appeasement could create more mental worries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review found limited studies that used the DERS with breast cancer patients. However, some included participants with other types of cancer, and others focused on the total DERS score rather than on each of the DERS specific difficulties (Ashkhaneh et al, 2015 ; Chen, 2021 ; Firouzi et al, 2020 ; Noori et al, 2016 ; Vaughan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Unfortunately, the BC incidence rate is on the rise in Iranian women, and estimates show that BC is responsible for 30% of total cancers and 15% of cancer-induced deaths among women. [ 3 ] BC accounts for 23% of total cancers diagnosed in women in Iran, as reported by the Iran National Cancer Registry. [ 4 ] Although the treatment success has been a great endowment for prolonging patients’ lifetime, increasing patients’ survival alone is not sufficient because patients do not only want to survive but they also want to have a more untroubled life.…”
Section: Introductionmentioning
confidence: 99%